Translation Of Arabic Cultural Collocations In Literary Texts: A Case Study Of English Translations Of Naguib Mahfouz's Novel " Awlad Hartna" - Ahmad Obeidat, Adham Mousa (2021)
This study is mainly intended to investigate the translation of cultural collocations from Arabic into English in one of Naguib Mafouz’s novels Awlad Hartna. The novel has been translated into English into two versions, Children of Gebalawi by Philip Stewart (1981) and Children of the Alley by Peter Theroux (1988). In this study, three main objectives have been proposed. Firstly, analyzing the source text and the target texts profiles and highlighting the occurrences at the macro-level. Secondly, investigating the occurrences at micro-level by referring to a lexical element, i.e. cultural collocations to investigate the problems that translator may encounter during the translation of the text. Finally, the present study attempts to describe whether the cultural collocations have been domesticated or foreignized based on the type of equivalence achieved by the translators